A case series of scar endometriosis after cesarean section - Desai, Suruchi; Mistry, Hetal U; Parikh, Rashmi (Indian Journal of Case Reports, 2024)
Endometriosis is referred to the presence of functioning, ectopic endometrial tissue outside the pelvic cavity. Their occurrences after abdominal or pelvic surgeries especially cesarean section, at the site of scar incision, are documented. The patient experiences cyclical pain at the incision site related to the menstrual cycle. Imaging can be used to detect the lesion and medical management can be provided. However, in severe cases, total excision is recommended to avoid the chances of recurrence. Here, we present a case series of two cases of scar endometriosis after cesarean section, and both presented with cyclical pain in the abdomen. Medical management was provided for both cases.